COACHING ISLAMI UNTUK RESOLUSI KONFLIK RUMAH TANGGA DALAM MEWUJUDKAN KELUARGA SAKINAH - Widayanti, Ida S.; Prabowo, Swasto Imam Teguh (Institut PTIQ Jakarta, 2022)
This article discusses the role of Islamic coaching in shaping a sakinah family. A sakinah family is a family that lives in peace, happiness, and harmony. Islamic coaching can help families achieve this goal by facilitating Islamic self-learning and development processes. This article outlines the concept of Islamic coaching and sakinah family, and explains how Islamic coaching can be applied in the family to achieve this goal. The discussion includes Islamic coaching methods, techniques and strategies used in coaching, as well as the benefits of Islamic coaching for families in achieving sakinah goals. Research shows that Islamic coaching can improve family communication, knowledge, sensitivity, and skills, which in turn will form a strong and emotionally, mentally, and spiritually healthy sakinah family. This article provides a new perspective on the role of Islamic coaching in shaping a sakinah family, which ultimately can improve the quality of family life and society as a whole